Ilmugo / Muhammad Zikri Amni Mohd Isa - Mohd Isa, Muhammad Zikri Amni (Universiti Teknologi MARA, Kedah, 2025)
Learning poverty is a serious issue in Malaysia, especially among children starting Standard 1 who struggle with basic reading and math. This research focuses on creating an educational tool for preschool children aged 4–6 in poverty-stricken and rural areas. The goal is to help them build a strong foundation in literacy and numeracy through fun and interactive activities. The tool uses a modular design, making it adaptable for different learning situations, easy to store, and simple to transport. Its bright and engaging design helps capture children's attention, keeping them motivated to learn. By combining learning with play, the tool helps children improve their reading and counting skills while also developing creativity, social skills, and problem-solving abilities. This product is designed to address challenges faced by children in poverty, such as limited access to quality materials and under-resourced schools. It’s also made to be affordable, durable, and easy to use, ensuring it can reach underserved communities. The project aims to make a real difference in reducing learning poverty, giving children the skills they need for a better future.